Laying the Foundation of the Economic System during the Time of the Prophet Saw in Medina - Hidayat, Dzulfikri; Mawardi, Kholid; Prasetya, Dimas (International Proceedings of Nusantara Raya, 2022)
In the early days of the Prophet Muhammad's proselytizing, he did not directly deal with economic problems because he had to focus onspreading Islam. The Prophet's economic activities were only carried out while in Medina by managing the government while managing theeconomy. Supported by the command of Allah Almighty. In the Qur'an surah Al Baqarah verse 275, where it is explained that we as Muslimsare encouraged to trade and are prohibited from staying away from usury. Based on this, it can be said that Islam is also very concerned abouteconomic activities. It will be Allah Almighty. Educating his servants through the intermediary of the Prophet Muhammad SAW, one ofwhich was by setting an example in the form of economic system activity at that time. This research is a qualitative research using theliterature study method. Based on the data that has been collected, several things were found that became the basis of the economic systemat the time of the Prophet.